Customer Satisfaction as a Mediator of the Influence of E-Service Quality and Customer Trust on Customer Loyalty Among Online Ride-Hailing Application Users - Nurul Huda; Desy Ariani Citrasari (J-Mabes: Jurnal Manajemen, Akuntansi, Bisnis Dan Studi Ekonomi Syariah, 2025)
Online ride-hailing applications continue to grow rapidly, making digital service quality, customer trust, and user loyalty increasingly important factors in maintaining competitiveness. In this context, customer satisfaction is often considered a mediating factor that connects the influence of e-service quality and trust on loyalty. This study aims to examine the mediating role of customer satisfaction in the relationship between e-service quality and customer trust toward user loyalty in ride-hailing applications. A quantitative approach was applied using a literature review method. Secondary data were gathered from various sources such as books, academic journals, and theses to analyze the reciprocal relationships among the variables. The findings indicate that all hypotheses from previous studies are supported, showing significant and positive relationships between digital service quality and customer trust toward satisfaction and loyalty. Customer satisfaction functions as an effective mediator, channeling the influence of e-service quality and trust into stronger customer loyalty. In other words, improvements in service quality and customer trust lead to higher satisfaction, which in turn enhances user loyalty.